Construção da paz sustentável na Guiné-Bissau - Gomes, Marcelino (2022)
This paper analyses the peacebuilding process conducted by the United Nations Peace-building Mission in Guinea-Bissau (UNIOGBIS) and the Economic Community of West African States (ECOWAS) participation in the process of guaranteeing institutional se-curity in the country through ECOWAS Mission in Guinea-Bissau (ECOMIB). For this, it is evaluated the period between 1999, the time where the UN established its peacebuild-ing mission in Guinea-Bissau, and 2020, the year in which all peacebuilding missions in Guinea were ended. The objective is to demonstrate whether such peacebuilding practices carried out by these missions referred to above have effectively contributed to the construction of integral peace, as well as to rethink and propose alternative ways of involvement of international and regional partners in the process of making sustainable peacebuilding in this little West African paradise. The chapters that make up this dissertation reflect the causes of constant political insta-bility in Guinea-Bissau and the efforts undertaken in the search for a lasting peace in Guinea, analysing processes of transformation and consolidation of this peace at a politi-cal, social, security and economic level. Without neglecting, however, the approaches, actors and contexts that are fundamental elements of analysis in the mapping of peace-building in Guinea. In this way, and with a clear conceptual and theoretical framing ob-jective, the present abstract serves as a gateway of the following analyses which are more focused in the several aspects identified here, from causes of conflicts to the sustainability of peacebuilding in Guinea-Bissau.